Can therapeutic drug monitoring optimize exposure to piperacillin in febrile neutropenic patients with haematological malignancies? A randomized controlled trial. (7th May 2015) - Sime, Fekade Bruck; Roberts, Michael S.; Tiong, Ing Soo; Gardner, Julia H.; Lehman, Sheila; Peake, Sandra L.; Hahn, Uwe; Warner, Morgyn S.; Roberts, Jason A.
Abstract : Regular TDM may be necessary to ensure adequate exposure of febrile neutropenic patients to piperacillin/tazobactam. However, whether the costs are justified by a better outcome requires further study in a randomized controlled clinical trial. Abstract: Objectives: The objectives of this study were to describe piperacillin exposure in febrile neutropenia patients and determine whether therapeutic drug monitoring (TDM) can be used to increase the achievement of pharmacokinetic (PK)/pharmacodynamic (PD) targets. Methods: In a prospective randomized controlled study (Australian New Zealand Registry, ACTRN12615000086561), patients were subjected to TDM for 3 consecutive days. Dose was adjusted in the intervention group to achieve a free drug concentration above the MIC for 100% of the dose interval (100% fT >MIC ), which was also the primary outcome measure. The secondary PK/PD target was 50% fT >MIC . Duration of fever and days to recovery from neutropenia were recorded. Results: Thirty-two patients were enrolled. Initially, patients received 4.5 g of piperacillin/tazobactam every 8 h or every 6 h along with gentamicin co-therapy in 30/32 (94%) patients. At the first TDM, 7/32 (22%) patients achieved 100% fT >MIC and 12/32 (38%) patients achieved 50% fT >MIC . Following dose adjustment, 11/16 (69%) of intervention patients versus 3/16 (19%) of control patients ( P  = 0.012) attained 100% fT >MIC, and 15/16 (94%) of intervention patients versus 5/16 (31%) of control patients ( P  = 0.001) achieved 50% fT >MIC . After the third TDM, the proportion of patients attaining 100% fT >MIC improved from a baseline 3/16 (19%) to 11/15 (73%) in the intervention group, while it declined from 4/16 (25%) to 1/15 (7%) in the control group. No difference was noted in the duration of fever and days to recovery from neutropenia. Conclusions: Conventional doses of piperacillin/tazobactam may not offer adequate piperacillin exposure in febrile neutropenic patients. TDM provides useful feedback of dosing adequacy to guide dose optimization.